Development of interactive storybook / Maslizawati Mohamad Masnan - Mohamad Masnan, Maslizawati (Faculty of Information Technology and Quantitative Sciences, 2005)
The technological applications and especially the use of multimedia courseware have become more common in today's education. The use of interactive storybooks may make easy for children's reading. This research, project is conducted to develop multimedia based interactive storybook. Interactive storybooks are becoming prevalent in educations as one way to teach children moral value and even technology itself. It also allows children to interact with the story. Other than that, interactive storybooks are becoming increasingly important in developing children's literacy. ADDIE model are choose to be the methodology for developing this courseware. It provide step by step in developing computer based instruction. It is suitable because ADDIE model is an iterative instructional design process, where the resuhs of the formative evaluation of each phase may lead the instructional designer back to any previous phase. It is hope that this development of interactive storybook will give many benefits toward many individual such as children, parent and teacher.